Combined treatment of calcium chloride and ε-polylysine maintains postharvest storage quality of dandelions ( Taraxacum antungense Kitag.) by regulating phenylpropanoid metabolism - Zhou 周鑫, Xin; Shi 施鑫园, Xinyuan; Wang 王明月, Mingyue; Jiang 姜雨璐, Yulu; Wang 王含菲, Hanfei; Wang 王斯瑶, Siyao; Zhou 周倩, Qian; Wu 吴杰, Jie (Food quality and safety, 2025)
As a leafy vegetable, dandelion (Taraxacum antungense Kitag.) leaves are subject to senescence, such as yellowing and even decay, during postharvest storage. Calcium chloride (CaCl2) and ε-polylysine (ε-PL) treatments can safely and effectively improve the postharvest quality of fruits and vegetables. To improve the storage quality, dandelions were treated with 0.5% (w/v) CaCl2 and 0.9 g/L ε-PL and stored at 4±0.5 ºC. The results showed that the combination treatment of CaCl2 and ε-PL (CaCl2+ε-PL treatment) could effectively delay the yellowing and chlorophyll content decline, as well as reduce the browning index, when compared with those of the control and single treatments. The CaCl2+ε-PL treatment also enhanced the synthesis and accumulation of secondary metabolites. The combination treatment could significantly enhance the enzyme activities of phenylalanine ammonia-lyase (PAL), 4-coumarate-CoA ligase (4CL), and cinnamate 4-hydroxylase (C4H) in phenylpropanoid metabolism and up-regulate the expression levels of TaPAL, Ta4CL, and TaC4H. Meanwhile, ε-PL treatment was more effective than CaCl2 treatment in promoting the expression of these genes. Correlation analysis indicates that the transcription levels and activities of the three enzymes, as well as the contents of secondary metabolites, are linked to the quality changes of dandelions treated with CaCl2 + ε-PL during cold storage. Principal component analysis (PCA) was used to assess the storage quality of dandelions during cold storage, and the results showed the following rankings: CaCl2+ε-PL>ε-PL>CaCl2>control. These findings suggest that CaCl2+ε-PL treatment can improve the postharvest storage quality of dandelions by modulating the phenylpropane metabolic pathway.